The Mechanistic Role of the Central American Seaway in a GFDL Earth System Model. Part 1: Impacts on Global Ocean Mean State and Circulation. Issue 7 (27th July 2018) - Sentman, Lori T.; Dunne, John P.; Stouffer, Ronald J.; Krasting, John P.; Toggweiler, J. R.; Broccoli, Anthony J.
Abstract: To explore the mechanisms involved in the global ocean circulation response to the shoaling and closure of the Central American Seaway (CAS), we performed a suite of sensitivity experiments using the Geophysical Fluid Dynamics Laboratory Earth System Model (ESM), GFDL‐ESM2G, varying only the seaway widths and sill depths. Changes in large‐scale transport, global ocean mean state, and deep ocean circulation in all simulations are driven by the direct impacts of the seaway on global mass, heat, and salt transports. Net mass transport through the seaway into the Caribbean is 20.5–23.1 Sv with a deep CAS but only 14.1 Sv for the wide, shallow CAS. Seaway transport originates from the Antarctic Circumpolar Current in the Pacific and rejoins it in the South Atlantic, reducing the Indonesian Throughflow and transporting heat and salt southward into the South Atlantic, in contrast to present‐day and previous CAS simulations. The increased southward salt transport increases the large‐scale upper ocean density, and the freshening and warming from the changing ocean transports decreases the intermediate and deep water density. The ocean circulation pathway with a CAS traps heat in the Southern Hemisphere oceans and reduces the northern extent of Antarctic Bottom Water penetration in the Atlantic, strengthening and deepening Atlantic meridional overturning, in contrast to previous studies. In all simulations, the seaway has a profound effect on the global ocean mean state and alters deep water mass properties and circulation in the Atlantic, Indian, and Pacific basins, with implications for changing deep water circulation as a possible driver for changes in long‐term climate. Key Points: Independent of the shoaling stage, the Central American Seaway altered the ocean mean state and deep water properties globally The seaway provided a shortcut for Pacific water, transporting heat and salt to the South Atlantic The seaway suppressed Antarctic Bottom Water northward extent, allowing North Atlantic Deep Water to deepen and slightly strengthen